2015
DOI: 10.1007/s11356-015-4903-y
|View full text |Cite
|
Sign up to set email alerts
|

Low level impurities in imported wheat are a likely source of feral transgenic oilseed rape (Brassica napus L.) in Switzerland

Abstract: In Switzerland, the cultivation of genetically modified (GM) oilseed rape (Brassica napus L.) and the use of its seeds for food and feed are not permitted. Nevertheless, the GM oilseed rape events GT73, MS8×RF3, MS8 and RF3 have recently been found in the Rhine port of Basel, Switzerland. The sources of GM oilseed rape seeds have been unknown. The main agricultural good being imported at the Rhine port of Basel is wheat and from 2010 to 2013, 19% of all Swiss wheat imports originated from Canada. As over 90% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…It can be assumed that wheat and barley samples contained low-level contamination with grains from other plant species as it has been described in other investigations, for instance, imported wheat with transgenic oilseed rape in Switzerland. 34 Alternatively, the presence of the nptII gene in a sample can be explained by possible contamination with environmental bacteria containing the nptII gene with a similar sequence. 35 Grains and seeds intended for the production of animal feed are a potential source of GMOs entering the territory of Latvia.…”
Section: Discussionmentioning
confidence: 99%
“…It can be assumed that wheat and barley samples contained low-level contamination with grains from other plant species as it has been described in other investigations, for instance, imported wheat with transgenic oilseed rape in Switzerland. 34 Alternatively, the presence of the nptII gene in a sample can be explained by possible contamination with environmental bacteria containing the nptII gene with a similar sequence. 35 Grains and seeds intended for the production of animal feed are a potential source of GMOs entering the territory of Latvia.…”
Section: Discussionmentioning
confidence: 99%
“…These four sites were ports and railway stations on the borders to France and Italy. The feral plants probably originated from spillage of contaminated OSR seed from freight trains (Hecht et al, 2014;Schulze et al, 2014Schulze et al, , 2015. Spillage of GM OSR seeds along transportation routes was also confirmed in Japan where cultivation of GM OSR is also prohibited (Saji et al, 2005;Kawata et al, 2009;Nishizawa et al, 2009Nishizawa et al, , 2010Aono et al, 2011;Mizuguti et al, 2011), the United States (in North Dakota 80% of feral OSR proved to be GM: Schafer et al, 2011;Sagers et al, 2012) and Canada (Yoshimura et al, 2006;Knispel et al, 2008;Beckie and Warwick, 2010;Knispel and McLachlan, 2010).…”
Section: Oilseed Rape As a Model System For Seed Spillage Along Transmentioning
confidence: 92%
“…An additional way for seed dispersal is contamination in other goods. Wheat imports from Canada were identified as potential source for contamination with GM OSR seeds (GT73, MS8 × RF3, MS8, and RF3) in the Rhine port of Basel and in processing facilities of two grain mills in Switzerland (Schulze et al, 2015). Imported wheat, a main agricultural goods handled at the Rhine port of Basel, may contain a low level of impurities of GM OSR (impurity in wheat imported from Canada is estimated to be 0.005% at average).…”
Section: Weed Management and Impurities In Imported Goodsmentioning
confidence: 99%
“…Another study confirmed these findings and identified hot spots of transgenic plants at locations were unloading takes place (Hecht et al 2014). These hot spots were ports and railway stations bordering to France and Italy, despite Switzerland's import ban (Schulze et al 2015.…”
Section: Switzerlandmentioning
confidence: 99%